DNA barcoding techniques used to identify the shared ichthyofauna between the Pantanal floodplain and Upper Parana River - da Costa-Silva, Guilherme J. [UNESP]; Yuldi Ashikaga, Fernando [UNESP]; Kioko Shimabukuro Dias, Cristiane [UNESP]; Garcia Pereira, Luiz Henrique; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Taylor & Francis, 2018)
The biological invasion process is widely debated topic, as the population depletion of some species and the extinction of others are related to this process. To accelerate the identification of species and to detect non-native forms, new tools are being developed, such as those based on genetic markers. This study aimed to use Barcode DNA methodology to identify fish species that had translocated between the Parana and Paraguay River Basins. Based on a database of two studies that were conducted in these regions, 289 sequences of Cytochrome Oxidase C subunit 1 (COI) were used for General Mixed Youle Coalecent (GMYC) analysis, including 29 morphospecies that were sampled in both river basins. As a result, we observed that while some morphospecies have low variation, demonstrating a recent occupation of the basins, other morphospecies probably represent species complexes. A third of the morphospecies had well-defined lineages but not enough to be treated as different Molecular Operational Taxonomic Units (MOTUs). These results demonstrate that human interventions possibly participated in the distribution of some lineages. However, biogeographical historical processes are also important for the morphospecies distribution. The data suggest that the number of species that are present in these two basins is underestimated and that human actions can irreversibly affect the natural history of the species in these regions.
Keywords: cytochrome oxidase 1; DNA barcoding; neotropical species; Pantanal; Upper Parana River